Movement Demands of Rugby Sevens in Men and Women: A Systematic Review and Meta-Analysis. Issue 12 (December 2019) - Ball, Shane; Halaki, Mark; Orr, Rhonda
Abstract : Abstract: Ball, S, Halaki, M, and Orr, R. Movement demands of rugby sevens in men and women: A systematic review and meta-analysis. J Strength Cond Res 33(12): 3475–3490, 2019—Global positioning systems (GPS) provide comprehensive information of player movement demands in rugby 7's. Although studies have investigated the use of GPS within many field-based team sports, the application of GPS within rugby 7's remains unclear. The aim of this review was to evaluate the movement demands and conduct a meta-analysis on comparable GPS measures to assess player movement in rugby 7's. A systematic search of electronic databases Medline, SPORTDiscus, Cinahl, Web of Science, Scopus, and Embase was performed. The search strategy combined terms covering: global positioning systems AND rugby union. Studies were included if they contained rugby sevens' players monitored by GPS. Meta-analyses were conducted to provide a pooled mean and confidence intervals (CIs) on outcomes for data extracted from at least 3 studies. A total of 24 publications were eligible for review and included 661 (447 male and 214 female) rugby 7's players. Meta-analysis indicated that male players cover greater relative distance (male: 108.5 m·min −1, 95% CI [104.9–112.1] m·min −1, female: 100.3 m·min −1, 95% CI [96.0–104.7] m·min −1 ), distance at >12.6 km·h −1 (male: 449.3 m, 95% CI [427.0–471.5] m, female: 339.5 m, 95% CI [291.1–387.9] m) and >18.0 km·h −1 (male: 190.3 m, 95% CI [180.7–199.9] m, female: 129.9 m, 95% CI [99.9–159.8] m), and have a greater maximum velocity compared with female players (male: 29.8 km·h −1, 95% CI [29.2–30.4] km·h −1, female: 24.6 km·h −1, 95% CI [23.3–25.9] km·h −1 ), whereas relative distance is higher for the first half (109.5 m·min −1, 95% CI [99.1–120.0] m·min −1 ) compared with the second half (93.8 m·min −1, 95% CI [87.4–100.1] m·min −1 ) of match play across sexes and playing levels. Independent velocity zone classifications should apply for male and female players, whereas velocity thresholds should remain consistent across studies. Rugby 7's training intensity should vary between male and female players.